Synthesis of some 1,3-diazepine -4,7-diones derivatives (part 2) - Hussein, F. A.; Mahrnoud, M. J.; Tawfiq, M. T. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
1,3-0xazepine-4)-diones were prepared by c.ondensation of NÂ cinnamylideneareneamines with maleic anhydride, phthalic;; anhydride ,and 3-nitrophthalic anhydride. The oxazepjne::; were reacted with primary aromatic amine to give the corresponding 1 ,3–diazepine-4,7- diones.